Bride price and Christian marriage in Nigeria - Ademiluka, Solomon O. (HTS teologiese studies, 2021)
Payment of bride price is a popular tradition in Nigeria as in most parts of Africa. However, in Nigeria, the practice has virtually lost its traditional purpose of marriage validation and honouring because of the commercialisation by many parents. For this reason, some critics have called for a cancellation of the custom, as it has turned women to commodities to be bought and sold. This article examined the purpose of bride price in the traditional African setting, the changes that have crept into the practice over time, and the desirability or non-desirability of bride price payment for Christians in Nigeria. The article employed the exegetical method for the study of the relevant texts and, using the descriptive approach, it gathered and utilised material relevant for bride price payment, as practised in Nigeria. The author found that payment of bride price is not prohibited in the Bible. In the traditional African society, bride price served mainly as the legal exchange that validated marriage. It was discovered that charging exorbitant bride prices by Nigerian parents obliterated the original purpose of the custom. Commercialisation of bride price in this way is partially responsible for the increasing rate of late marriages and non-marriages amongst Christians. The inability to pay high bride prices had created a situation whereby young Christian men and women cohabit without legally getting married. Exorbitant bride price sometimes leads to domestic violence against women. It is for these reasons that some have considered payment of bride price unchristian, whilst others have called for its abolishment. Nevertheless, this study concluded that as payment of bride price is not prohibited in the Bible, it is not wrong for Christians to pay and receive bride prices. Moreover, if its traditional purpose is adhered to, payment of bride price need not cause women abuse. Its cancellation would amount to doing away with the original purpose of the practice, particularly the legitimisation and honouring of marriage. Therefore, rather than abolishing bride price, one would call for a return to its original purpose. More than recognising the value of bride price, the church in Nigeria has the responsibility to educate Christian parents on the adverse implications of charging exorbitant bride prices.Contribution: This article is a contribution in ethics of Christian marriage. It is relevant for educating Nigerian Christian parents against charging excessive bride prices.